Hubungan Ketahanan Pangan Keluarga dengan Status Gizi pada Wanita Usia Subur di Bendosari - Masyiithoh Ridha Efendi; Luluk Ria Rakhma; Firmansyah Firmansyah (Yayasan Literasi Sains Indonesia, 2025)
Nutritional status in women of reproductive age is strongly influenced by food security, which plays an essential role in maintaining health. This study aimed to examine the correlation between household food security and the nutritional status of women of reproductive age in the Bendosari Community Health Center area, which covers three villages: Mulur, Mertan, and Toriyo. A total of 162 participants were selected using a simple random sampling method in this cross-sectional research. Food security was assessed using the Household Food Insecurity Access Scale (HFIAS) consisting of nine items related to food access, while nutritional status was measured through Mid-Upper Arm Circumference (MUAC), which represents the amount of fat reserves in the body. Data were analyzed using the Chi-Square test with a significance level of p<0.05. Findings revealed that 70.4% of respondents had household incomes below the regional minimum wage, and 9.9% were categorized as malnourished. The Chi-Square test produced a p-value of 0.037 (p<0.05), indicating a significant association between food security and women’s nutritional status in Bendosari. Food security is affected by factors such as income, education, knowledge, and household size, while women’s nutritional status is shaped by eating behaviors that, if poor, may result in health complications. These results highlight the importance of strengthening household food security to minimize the risk of Chronic Energy Deficiency among women of reproductive age.